(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In this article, in order to increase the quality and effectiveness of primary education, students’ critical thinking, creative approach, and teamwork are developed by using the "4K" model (critical thinking, creativity, collaboration, communication) in new generation textbooks created for grades 1-4. and it is thought that it is aimed at developing communication skills.